If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50 = -2(21 + -1m) + 4(m + -4) 50 = (21 * -2 + -1m * -2) + 4(m + -4) 50 = (-42 + 2m) + 4(m + -4) Reorder the terms: 50 = -42 + 2m + 4(-4 + m) 50 = -42 + 2m + (-4 * 4 + m * 4) 50 = -42 + 2m + (-16 + 4m) Reorder the terms: 50 = -42 + -16 + 2m + 4m Combine like terms: -42 + -16 = -58 50 = -58 + 2m + 4m Combine like terms: 2m + 4m = 6m 50 = -58 + 6m Solving 50 = -58 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 50 + -6m = -58 + 6m + -6m Combine like terms: 6m + -6m = 0 50 + -6m = -58 + 0 50 + -6m = -58 Add '-50' to each side of the equation. 50 + -50 + -6m = -58 + -50 Combine like terms: 50 + -50 = 0 0 + -6m = -58 + -50 -6m = -58 + -50 Combine like terms: -58 + -50 = -108 -6m = -108 Divide each side by '-6'. m = 18 Simplifying m = 18
| X^2+4+4x=0 | | -2x-6=3y-12 | | 2(1-x)=2x+3(2-3x) | | 5x-(x-2)=3(x-4) | | (5v-7)(9+v)=0 | | (9x+8)=9 | | 7x-16=40 | | 3.1x=2.3x+6.4 | | 5x-15=2x-8 | | (9x+8)2=9 | | 13x-(5x-3)=27 | | 6(2x-7)-2(x+3)-16= | | 5(x+4)+3=7x-2(x-5) | | 4x^2=60 | | 10x-38=4x+a | | 4x-3y=7 | | 6(2x-5)-4(x+4)-16x= | | 4(3x-9)=20(x+4) | | 7-0.3x=4 | | 24x-18-16x=4(2x-5)+2 | | 34-5x=15+4x | | 7(x+3)-8=4x+3(3+x) | | 4x+y=-1 | | 80-5x=13x+18 | | 1xy^2-2x+5xy^2= | | 5(3x-8)-4(x+1)-18x= | | -4p+5+5p=12 | | 4x-1x+140=40 | | 5x^2+3x=8x | | -21=-7z | | 11-9x=159-37x | | B=qn+q |